Mechanical pruning and soil organic amending in vineyards of Syrah: effects on grape composition - Manuel Botelho (OENO One, 2021)
The interaction of mechanized pruning systems and soil organic amending is a way to increase vine productivity. However, since the increase in productivity may have effects on grape composition, this study aims to understand the effects of the interaction between these two practices.